NON-ISOTHERMAL STUDIES on CRYSTALLIZATION KINETICS of TELLURITE 20Li(2)O-80TeO(2) GLASS - Araujo, E. B. [UNESP]; Idalgo, E. [UNESP] (Springer, 2009)
Structural and thermal properties of the 20Li(2)O-80TeO(2) glass were studied using X-ray diffraction analysis and differential scanning calorimetry techniques to understand and control the crystallization process on this glass. The gamma-TeO2, gamma-TeO2 and gamma-Li2Te2O5 phases were identified during the crystallization in this glass. Activation energies and Avrami exponent n were calculated from non-isothermal measurements for glasses with different particle size. The mean values n of Avrami exponent were obtained for glasses with 63-75 and 45 - 63 mu m particle sizes such as (n) over bar (1)< <(n)over bar>(2)< <(n)over bar>(3), but glasses with particle size 38 - 45 mu m and smaller than 38 mu m presented (n) over bar (1)approximate to(n) over bar (2)< <(n)over bar>(3).
Keywords: crystallization; glass; tellurium